LEGAL ARGUMENTATION; The Perspective of Science of Law and Islamic of Law - Edy Faishal Muttaqin (Madania: Jurnal Ilmu-Ilmu Keislaman, 2012)
Legal Argumentation that is a scientific skill in law to be useful as a base consideration for legal experts in obtaining and provide legal solutions. Deftness is not as easy as scientific imagined people because it requires the willingness and ability to develop special someone power he thought. Legal Argumentation appears as a response or feedback from the absence of legal problem leads to the rise of dissenting opinion (discourse or polemic) in society. Legal problem everlastingly appearing along with dynamics and complexity people bringing implication of social conflict, social occurrence so the argument law is expected to any legal problems can be resolved quickly, accurate, safe, and properly.